A COMMUNITY-BASED NUTRITION EDUCATION INTERVENTION WITH FUNCTIONAL FOOD DEMONSTRATION FOR CAR FREE DAY PARTICIPANTS IN JOMBANG REGENCY - Putri, Diah Pitaloka; Fithriah, Alfi Rahmatillah Nur; Agrisdian, Zerly; Safitri, Puput; Diba, Nadia Farah (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2025)
The increasing consumption of low-nutrient snack foods in Indonesia underscores the need for community-based nutrition education interventions that promote healthier food choices using local resources. This community service program aimed to improve nutrition awareness and knowledge of healthy snack selection among Car Free Day participants in Jombang Regency through a media-based nutrition education approach combined with functional food demonstrations. The intervention was conducted during the National Nutrition Day event and targeted community members attending Car Free Day activities. Methods included individual nutrition counseling, the use of posters and leaflets, product demonstrations, and the distribution of bok choy sticks and rhizome-based powders made from ginger, turmeric, and Javanese ginger. Program evaluation employed descriptive methods, including observation of participant engagement, documentation of attendance, and collection of qualitative verbal feedback. The indicators assessed were participant participation, interaction during education sessions, expressed understanding of balanced nutrition messages, and acceptance of the functional food products. The activity demonstrated high participant engagement and positive acceptance of local functional foods. However, due to the absence of quantitative pre–post measurements, the findings should be interpreted as preliminary.